Open access wireless markets - DOYLE, LINDA (My University, 2016)
This paper describes an open access market for capacity. Open access means that in real-time, network capacity cannot be withheld—capacity is priced dynamically by the marginal demand during congestion. The paper offers the open access market as a means for managing growing spectrum demand and as an alternative to naked spectrum sharing. The paper describes the parameters of the open access market showing that it can be implemented using today's technology and without significant regulatory change. The paper discusses how the open access market can eliminate barriers at the service level, allowing any number of service providers to compete in response to market drivers. The paper emphasises that the spatial and temporal granularity at which capacity can be purchased, allows for smaller entities to acquire resources, which is important for new entrants testing the water and those with non-standard business plans. The paper also shows how the open access market can provide a path to achieve greater sharing and efficient trade in the future.
PUBLISHED